Surgery: Pearls in Ancient Mesopotamia - Ali, Nadeen Agou; Al-Hijaji, Mohammed (Scientific Journal of Medical Research, 2019)
Many surgical disciplines date their origin to ancient Mesopotamia. The existing documents from the Assyro-Mesopotamian era which have reference to medicine and surgery are rare and precious. The medical treasures remain under underexplored. In this article, our purpose is to shed light on what has been written in the literature on Mesopotamians’ surgical practice.